2017
DOI: 10.1016/j.scitotenv.2017.07.236
|View full text |Cite
|
Sign up to set email alerts
|

Application of phytoscreening to three hazardous waste sites in Arizona

Abstract: The great majority of prior phytoscreening applications have been conducted in humid and temperate environments wherein groundwater is relatively shallow (~1-6m deep). The objective of this research is to evaluate its use in semi-arid environments for sites with deeper groundwater (>10m). To that end, phytoscreening is applied to three chlorinated-solvent hazardous-waste sites in Arizona. Contaminant concentrations were quantifiable in tree-tissue samples collected from two of the sites (Nogales, Park-Euclid).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Significant differences in tree-tissue VOC concentrations as a function of tree species were also observed in prior analyses of phytoscreening data collected from sites with deeper groundwater 11,37 . Sorek et al 11 reported significant differences in concentrations as a function of tree species for multiple sampling sites in Tel Aviv.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Significant differences in tree-tissue VOC concentrations as a function of tree species were also observed in prior analyses of phytoscreening data collected from sites with deeper groundwater 11,37 . Sorek et al 11 reported significant differences in concentrations as a function of tree species for multiple sampling sites in Tel Aviv.…”
Section: Resultsmentioning
confidence: 61%
“…core or branch) is likely a primary source of variability given that prior studies have indicated that tissue concentrations measured for trunk core samples are significantly higher than those measured for branch or leaf samples for the same conditions. 6,8, 10, 37 Thus, the aggregate data were first parsed to include only those representing trunk core samples (95 out of the 100 total samples). A correlation between core tissue and groundwater concentrations was determined to have an r-squared of 0.56 for the aggregated data set.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this way, natural resources are consumed while the amount of waste is not reduced, so that only in the short time can the problem be mitigated or solved. Some authors [8,9] examined various methods by which it is possible to monitor the impact of hazardous waste from landfills on the environment, while other authors [10,11] examined the possibility of legislation to solve the problem of illegal landfills or to find ways for more efficient networking between hazardous waste producers and plants that deal with its processing. Additionally, the problem of hazardous waste, such as bottom ash [12] or fly ash [13][14][15], can be solved by applying it in the construction industry, as a substitute for cement in the production of mortar and concrete.…”
Section: Introductionmentioning
confidence: 99%